High burden of CMV infections after simultaneous pancreas-kidney transplantation—a nationwide cohort study - Ahopelto, Kaisa; Grasberger, Juulia; Ortiz, Fernanda; Ekstrand, Agneta; Nordin, Arno; Lempinen, Marko; Helanterä, Ilkka (Frontiers in Transplantation, 2024)
Cytomegalovirus (CMV) infections remain a common problem after solid-organ transplantation. We characterized the burden of CMV infections, and adverse events of CMV prophylaxis after simultaneous pancreas-kidney transplantation (SPK). We included all SPK patients (n=236) since 2010 in our country. Immunosuppression was ATG, tacrolimus, mycophenolate, and steroids. Valganciclovir prophylaxis was given to all CMV D+/Rpatients for six months, and to seropositive SPK patients for three months since February 2019. CMV DNAemia was monitored with quantitative PCR from plasma. Among D+/R-SPK recipients, post prophylaxis CMV infection was detected in 41/60 (68%) during follow-up. In seropositive SPK recipients with no prophylaxis, CMV infection was detected in 53/95 (56%), vs. 28/78 (36%) in those who received 3 months of prophylaxis (P=0.01). CMV was symptomatic in 35 (15%) patients, of which 10 required hospitalization. Mean duration of viremia was 28 days (IQR 21-41). Leukopenia was detected in 63 (46%) of the 138 patients with valganciclovir prophylaxis. 7/122 (6%) of the CMV infections detected were defined as refractory to treatment, and three patients had confirmed ganciclovir resistance. SPK recipients experience a high burden of CMV infections despite CMV prophylaxis. Leukopenia is common during valganciclovir prophylaxis. ( 191words) * P=0.01, compared to seropositive patients with no prophylaxis ** P<0.001, compared to seropositive patients *** P<0.001, compared to seropositive patients with no prophylaxis **** P=0.04, compared to seropositive patients with no prophylaxis ***** P=0.01, compared to seropositive patients with no prophylaxis # P<0.001, compared to seropositive patients with no prophylaxis All other differences are nonsignificant.